Enhanced immune response against HIV-1 induced by a heterologous DNA prime-adenovirus boost vaccination using mannosylated polyethyleneimine as DNA vaccine adjuvant - Li M (Dove Medical Press, 2013)
Man Li,1 Yuhong Jiang,1 Chaoqun Xu,2 Zhirong Zhang,1 Xun Sun11Key Laboratory of Drug Targeting, Ministry of Education, West China School of Pharmacy, Sichuan University, Chengdu, People’s Republic of China; 2Sichuan Academy of Chinese Medicine Sciences, Chengdu, Sichuan, People’s Republic of ChinaBackground: The heterologous deoxyribonucleic acid (DNA) prime-adenovirus (AdV) boost vaccination approach has been widely applied as a promising strategy against human immunodeficiency virus (HIV)-1. However, the problem of inefficient delivery and lack of specificity of DNA vaccine remains a major issue. In this paper, to improve the transfection of DNA vaccine and realize dendritic cell targeting, we used mannosylated polyethyleneimine (man-PEI) as a DNA vector carrier.Method: The DNA plasmid encoding antigen HIV gag fragment was constructed by polymerase chain reaction. Then the DNA plasmid was complexed with man-PEI. The in vitro transfection efficiency of man-PEI/DNA was analyzed on DC 2.4 cells. Mice were primed with 25 µg pVAX1-HIV gag plasmid complexed with man-PEI, 100 µg naked pVAX1-HIV gag plasmid, or empty pVAX1 vector and boosted by AdV encoding the same antigen. The antibody titer, CD4+ and CD8+ T-cell response, as well as interferon-γ and interleukin-4 levels in serum and in splenocytes culture were analyzed using flow cytometry or enzyme-linked immunosorbent assay to evaluate the immune response. To test a long-term effect of the vaccination regimen, CD8+ memory T-cell was also detected by flow cytometry.Results: The pVAX1-HIV gag was constructed successfully. The in vitro transfection efficiency in dendritic cells was significantly higher than naked DNA plasmid. Compared with 100 µg naked DNA/AdV group, the immunoglobulin G2a antibody titer, T-cell response percentage, and cytokine production level induced by man-PEI/DNA/AdV group were significantly higher at a lower DNA dose. Also, the man-PEI/DNA could stimulate a memory CD8+ T-cell response.Conclusion: Owing to the adjuvant effect of man-PEI, the man-PEI/pVAX1-HIV gag priming plus AdV boosting strategy proved to be a potent vaccine candidate against HIV, which could induce a stronger immune response with a lower DNA dose.Keywords: human immunodeficiency virus, heterologous vaccination, mannosylated polyethyleneimine, DNA delivery, immune response